faktor-faktor yang berhubungan dengan kejadian hipertensi pada akseptor kontrasepsi hormonal di wilayah puskesmas kandang kecamatan kampung melayu kota bengkulu - nuril absari (STIKes CHMK, 2020)
ABSTRACT Hypertension is a medical condition in which the blood pressure is elevated persistently beyond normal that could lead to illness morbidity or death mortality. The purpose of this study is to determine Factors who Associated with Incidence of Hypertension on Acceptor of Hormonal Contraception in Area of Kandang Primary Health Care Kampung Melayu Sub-District Bengkulu City. The study take place in Area of Kandang Primary Health Care Kampung Melayu Sub-District Bengkulu City from july to august 2018. This study used survey analytic approach with cross sectional design. Population in this study were all Acceptor of Hormonal Contraception in Area of Kandang Primary Health Care Kampung Melayu Sub-District Bengkulu City in 2017. Sampling technique used Accidental Sampling with the amount of 33 people. Collecting data in this study used primary data with spreaded questionnaire to Acceptor of Hormonal Contraception in Area of Kandang Primary Health Care Kampung Melayu Sub-District Bengkulu City.The result of this study showed: from 33 sample there were 12 people (36,4%) experienced, 19 people (57,6%) with age of >35 years, 23 people (69,7%) with prolonged utilization >2 years, 23 people (69,7%) with hypertension history. There is significant relationship between Age with Incidence of Hypertension on Acceptor of Hormonal Contraception in Area of Kandang Primary Health Care Kampung Melayu Sub-District Bengkulu City with moderate category relationship. From the Contingency coefficient test C=0,462 which means ρ=0,003 <α=0,05 that it is significant. (6) there is significant relationship between Prolonged Utilization with Incidence of Hypertension on Acceptor of Hormonal Contraception in Area of Kandang Primary Health Care Kampung Melayu Sub-District Bengkulu City with moderate category relationship. From the Contingency coefficient test C=0,446 which means ρ=0,005 <α=0,05 that it is significant. (7) there is significant relationship between Hypertension History with Incidence of Hypertension on Acceptor of Hormonal Contraception in Area of Kandang Primary Health Care Kampung Melayu Sub-District Bengkulu City with moderate category relationship. From the Contingency coefficient test C=0,446 which means ρ=0,004 <α=0,05 that it is significant. Midwives whose work at public health centre should give inform consent about advantages, weakness and side effect of using contraception method that could lead hypertension for using it more than 2 years or at age 35 up, midwives also can give counseling to the acceptor to choose the best contraception methods. Keywords: Age, Prolonged Utilization Hormonal Contraception, Hypertension Histor